Composition‐Tuned Wide Bandgap Perovskites: From Grain Engineering to Stability and Performance Improvement - Zhou, Yang; Jia, Yong‐Heng; Fang, Hong‐Hua; Loi, Maria Antonietta; Xie, Fang‐Yan; Gong, Li; Qin, Min‐Chao; Lu, Xin‐Hui; Wong, Ching‐Ping; Zhao, Ni (Advanced functional materials, 2018)
Wide bandgap (WB) organic–inorganic hybrid perovskites (OIHPs) with a bandgap ranging between 1.7 and 2.0 eV have shown great potential to improve the efficiency of single‐junction silicon or thin‐film solar cells by forming a tandem structure with one of these cells or with a narrow bandgap perovskite cell. However, WB‐OIHPs suffer from a large open‐circuit voltage (Voc) deficit in photovoltaic devices, which is associated with the phase segregation of the materials under light illumination. In this work the photoinstability is demonstrated and Voc loss can be addressed by combining grain crystallization and grain boundary passivation, achieved simultaneously through tuning of perovskite precursor composition. Using FA0.17Cs0.83PbI3–xBrx (x = 0.8, 1.2 1.5, and 1.8), with a varied bandgap from 1.72 to 1.93 eV, as the model system it is illustrated how precursor additive Pb(SCN)2 should be matched with a proper ratio of FAX (I and Br) to realize large grains with defect‐healed grain boundaries. The optimized WB‐OIHPs show good photostability at both room‐temperature and elevated temperature. Moreover, the corresponding solar cells exhibit excellent photovoltaic performances with the champion Voc/stabilized power output efficiency reaching 1.244 V/18.60%, 1.284 V/16.51%, 1.296 V/15.01%, and 1.312 V/14.35% for WB‐OIHPs with x = 0.8, 1.2, 1.5, and 1.8, respectively. The photoinduced phase segregation in wide bandgap hybrid perovskites are greatly suppressed by combining grain crystallization and grain boundary passivation. As a result, the open‐circuit voltage (Voc) loss of the corresponding devices is highly reduced, demonstrating a monotonic increase of Voc with increasing of bandgap from 1.72 to 1.93 eV.